Warfarin skin necrosis mimicking calciphylaxis in a patient with secondary hyperparathyroidism undergoing peritoneal dialysis - Jee Eun Park; Seonggyu Byeon; Hee Kyung Kim; Seong Mi Moon; Ji Hoon Moon; Kee-Taek Jang; Byung-Jae Lee; Hye Ryoun Jang; Wooseong Huh; Dae Joong Kim; Yoon-Goo Kim; Ha Young Oh; et al. (The Korean Society of Nephrology, 2016)
Warfarin skin necrosis (WSN) is an infrequent complication of warfarin treatment and is characterized by painful ulcerative skin lesions that appear a few days after the start of warfarin treatment. Calciphylaxis also appears as painful skin lesions caused by tissue injury resulting from localized ischemia caused by calcification of small- to medium-sized vessels in patients with end-stage renal disease. We report on a patient who presented with painful skin ulcers on the lower extremities after the administration of warfarin after a valve operation. Calciphylaxis was considered first because of the host factors; eventually, the skin lesions were diagnosed as WSN by biopsy. The skin lesions improved after warfarin discontinuation and short-term steroid therapy. Most patients with end-stage renal disease have some form of cardiovascular disease and some require temporary or continual warfarin treatment. It is important to differentiate between WSN and calciphylaxis in patients with painful skin lesions.